Critical Evaluation of Potentiostatic Holds as Accelerated Predictors of Capacity Fade during Calendar Aging. Issue 5 (1st May 2022) - Schulze, Maxwell C.; Rodrigues, Marco-Tulio F.; McBrayer, Josefine D.; Abraham, Daniel P.; Apblett, Christopher A.; Bloom, Ira; Chen, Zonghai; Colclasure, Andrew M.; Dunlop, Alison R.; Fang, Chen; Harrison, Katharine L.; Liu, Gao; et al.
Abstract : Li-ion batteries will lose both capacity and power over time due to calendar aging caused by slow parasitic processes that consume Li + ions. Studying and mitigating these processes is traditionally an equally slow venture, which is especially taxing for the validation of new active materials and electrolyte additives. Here, we evaluate whether potentiostatic holds can be used to accelerate the diagnosis of Li + loss during calendar aging. The technique is based on the idea that, under the right conditions, the current measured as the cell voltage is held constant can be correlated with the instantaneous rate of side reactions. Thus, in principle, these measurements could capture the rate of capacity fade in real time . In practice, we show that this method is incapable of quantitatively forecasting calendar aging trends. Instead, our study demonstrates that potentiostatic holds can be applied for initial qualitative screening of systems that exhibit promising long-term stability, which can be useful to shrink the parameter space for calendar aging studies. By facilitating the identification of improved formulations, this approach can help accelerate innovation in the battery industry.